Legal Study on Village Government Authority in Village Assets Management - Josepus Julie Pinori (International Journal of Applied Business and International Management, 2020)
This study aims to analyze legals on village government authority in village assets management. The study was conducted at Tateli and Kanonang village, Minahasa Regency by legal research. The Empirical Legal Research method was used directly on informants in Minahasa Regency. The study finds that: (1) The authority of the village government in managing assets as a source of original village income is opaque. (2) The village decentralization system has not yet reached financial decentralization. (3) Village autonomy and autonomy of financial sector remains difficult to realize in Indonesia.